The efficiency of Soran M Medium in Selective Isolation of Antibiotic Producing Actinomycetes - Y. Noori, Ashwaq; I. Othman, Karwan; M. Othman, Maryia; T. Mustafa, Eman (Tikrit Journal of Pharmaceutical Sciences, 2023)
To assess the role of enriched constituents forming Soran M medium in selectiveisolation of antibiotic producing actinomycetes, six soil samples were collected inNovember 2016 from different sites in Soran, Erbil, Iraq. To culture soil samples spreadplatetechnique was used on Soran M and standard medium such as Arginine GlycerolSalt agar. Preliminary screening was done using cross-streak method against fourbacterial pathogenic strains and Candida albicans. Nine isolates from total 40actinomycetes isolates showed antimicrobial activities against pathogens. Themorphological and cultural characterization of these isolates was performed and showedthat 3 isolates belonged to the genus Nocardia while the others belonged to Streptomyces.The potential strain MB3 with both broad spectrum antibacterial and antifungal activitywas isolated on both media but showed different abilities to produce antibiotics. It wasidentified as Streptomyces sp. Findings from this investigation revealed that nutrientmedia with different composition affect the isolation of antibiotic producingactinomycetes with different activities.